Development of a Stability Criterion for Men’s Basketball Shoes During Mediolateral Cutting Maneuvers - Yara Izhiman; Lindee B. Calvert; Leora Tuulia Kri Meehan-Numminen; Zahab Ahsan; Brian Bigler; Eric A. Nauman (Annals of Biomedical Engineering, 2026)
Ankle and knee injuries are common in court sports such as basketball and tennis, where there is an emphasis on cutting maneuvers and cleats are not a viable footwear solution. Such maneuvers generate substantial lateral ground reaction forces with the potential to overcome native anatomic ankle stability. The goal of this study was to develop a simple criterion that could be applied to assess the design of basketball shoes in an effort to enhance ankle stability and subsequently reduce lower extremity injuries. The criterion relates the foot’s vertical force ( F v ) and mediolateral force ( F ml ) to the sole and wall thicknesses of the shoe through a critical ratio $$\frac{F_{v}t}{F_{ml}h}$$ F v t F ml h , where a critical ratio of is less than 1 denotes shoe instability. To evaluate our proposed criterion, a closed-form analysis combining force data from cutting movements characterized in previously published studies with simple geometric measurements of modern basketball shoes was conducted in nine shoe models. In addition, an experimental evaluation using a custom-built ankle model was carried out to validate the criterion on two of the shoe models. The ankle model included a prosthetic foot, steel shaft, double-U-joint, and load cell readout to acquire force and center of pressure associated with mediolateral ankle tipping. The experimental evaluation supported the validity of the instability envelope. Of the nine currently available shoe models evaluated here, none passed the criterion for all of the previously reported loading conditions and two demonstrated fundamental instabilities at the forefoot or heel.

International Consortium on Ageing-Related Pathologies (ICCARP) Audiovestibular Group: fostering international consensus to refine International Classification of Diseases (ICD-11) codes for hearing loss across the life course - Dialechti Tsimpida; Michael A. Akeroyd; Barry L. Bentley; Shuvarthi Bhattacharjee; Michael R. Bowl; Emma Broome; Stuart R. G. Calimport; Sian Calvert; Gary Christopher; Tom Dening; Silvia Di Bonaventura; Ankita Goswami; et al. (GeroScience, 2025)

Measuring changes in background dissolved gases to evaluate multi-component gas dissolution: Laboratory experiments and implications for stray gas monitoring - Madeline M. Calvert; Mitchell A. Davidson; Ariel Nunez Garcia; Kevin G. Mumford (Advances in Water Resources, 2024)

Inter-colony variation in predation, mercury burden and adult survival in a declining seabird - Anna M. Calvert; Sarah E. Gutowsky; David A. Fifield; Neil M. Burgess; Rachel Bryant; Gail S. Fraser; Carina Gjerdrum; April Hedd; Patricia L. Jones; Robert A. Mauck; Laura McFarlane Tranquilla; William A. Montevecchi; et al. (Science of The Total Environment, 2024)

Paleomagnetically defined brief lifespans for two large shield volcanoes in the Cascades Arc - Anthony F. Pivarunas; Dawnika L. Blatter; L.J. Patrick Muffler; Michael A. Clynne; Andrew T. Calvert; Lauren N. Harrison; Robert L. Christiansen (Journal of Volcanology and Geothermal Research, 2023)

Short‐term movement dynamics of the world’s largest sea cucumbers (genus Thelenota ) - Benjamin C. T. Gray; Luke A. Calvert; Steven W. Purcell (Marine Ecology, 2022)
Movement studies on marine animals can inform conservation and fishery management planning through data that explain likely dispersals and home‐ranging behaviours. Relatively few studies are documented for exploited marine invertebrates, despite many having a high ecological and commercial value. We assessed the diurnal movement patterns of Thelenota ananas and Thelenota anax , the world's largest sea cucumbers, which are highly exploited throughout the Indo‐Pacific. At two coral reef sites at Lizard Island, northern Australia, we tracked the 2‐hourly displacement of individuals from morning to nightfall. Movement of T . ananas was more reef‐associated and tortuous than T . anax . Displacement rates averaged 80 cm h −1 (±8 SE) for T . ananas and 73 cm h −1 (±20) for T . anax . Body size accounted for half of the variation in displacement for T . ananas . Mobility peaked in the late afternoon or early evening for both species, and animals tended to reverse their direction of travel after midday. The data reflect a pattern of animals meandering out from their reef shelters onto sandy lagoon floors to forage, before returning to the reefs. This empirical evidence offers further support that these holothuroids contribute to the formation of “reef halos”. The exceptionally high movement rates and patterns found in this study should inform the design of spatial management measures.

Compaction- and Shear-Induced Well Deformation in Tyra: Geomechanics for Impact on Production - P. M. T. M. Schutjens; P. Fokker; U. B. B. Rai; J. Kandpal; M. V. Cid Alfaro; N. D. Hummel; R. Yuan; F. Klever; S. De Gennaro; J. Vaibav; F. Bourgeois; M. Calvert; et al. (Rock Mechanics and Rock Engineering, 2019)

Multi-scenario Geomechanical Modeling for Investigating Well Deformation in the Deep Overburden Over a Compacting Reservoir in the North Sea - R. S. Yuan; M. A. Calvert; P. M. T. M. Schutjens; F. G. Bourgeois (Rock Mechanics and Rock Engineering, 2019)

Timescales of magmatic differentiation from alkali basalt to trachyte within the Harrat Rahat volcanic field, Kingdom of Saudi Arabia - Mark E. Stelten; Drew T. Downs; Hannah R. Dietterich; Gail A. Mahood; Andrew T. Calvert; Thomas W. Sisson; Hani Zahran; Jamal Shawali (Contributions to Mineralogy and Petrology, 2018)

Lava-ice interaction on a large composite volcano: a case study from Ruapehu, New Zealand - C. E. Conway; D. B. Townsend; G. S. Leonard; C. J. N. Wilson; A. T. Calvert; J. A. Gamble (Bulletin of Volcanology, 2015)

Variation in songbird migratory behavior offers clues about adaptability to environmental change - Anna M. Calvert; Stuart A. Mackenzie; Joanna Mills Flemming; Philip D. Taylor; Sandra J. Walde (Oecologia, 2012)

Reply to the comment on the article “40Ar/39Ar dating of tuff vents in the Campi Flegrei caldera (southern Italy): toward a new chronostratigraphic reconstruction of the Holocene volcanic activity” by Isaia et al. - L. Fedele; D. D. Insinga; A. T. Calvert; V. Morra; A. Perrotta; C. Scarpati (Bulletin of Volcanology, 2012)

40Ar/39Ar dating of tuff vents in the Campi Flegrei caldera (southern Italy): toward a new chronostratigraphic reconstruction of the Holocene volcanic activity - L. Fedele; D. D. Insinga; A. T. Calvert; V. Morra; A. Perrotta; C. Scarpati (Bulletin of Volcanology, 2011)

A missense mutation in Fgfr1 causes ear and skull defects in hush puppy mice - Jennifer A. Calvert; Skarlatos G. Dedos; Kelvin Hawker; Michelle Fleming; Morag A. Lewis; Karen P. Steel (Mammalian Genome, 2011)

Age, geochemical composition, and distribution of Oligocene ignimbrites in the northern Sierra Nevada, California: implications for landscape morphology, elevation, and drainage divide geography of the Nevadaplano - Elizabeth J. Cassel; Andrew T. Calvert; Stephan A. Graham (International Geology Review, 2009)

Postshield stage transitional volcanism on Mahukona Volcano, Hawaii - David A. Clague; Andrew T. Calvert (Bulletin of Volcanology, 2009)

Continuation of the New England Orogen, Australia, beneath the Queensland Plateau and Lord Howe Rise - N. Mortimer; F. Hauff; A. T. Calvert (Australian Journal of Earth Sciences, 2008)

Tool use changes multisensory interactions in seconds: evidence from the crossmodal congruency task - Nicholas P. Holmes; Gemma A. Calvert; Charles Spence (Experimental Brain Research, 2007)

An initial study into the use of microwave remediation of hexachlorobenzene treated soil using selected oxidants and coated graphite rods - Craig A. Calvert; Steven L. Suib (Journal of Soils and Sediments, 2007)

Comparison of in vitro cytotoxicity of Fusarium mycotoxins,deoxynivalenol, T-2 toxin and zearalenone on selected human epithelial cell lines - T. W. Calvert; K. E. Aidoo; A. G. G. Candlish; A. R. Mohd. Fuat (Mycopathologia, 2005)

North Atlantic phylogeography and large‐scale population differentiation of the seagrass Zostera marina L. - JEANINE L. OLSEN; WYTZE T. STAM; JAMES A. COYER; THORSTEN B. H. REUSCH; MARTIN BILLINGHAM; CHRISTOFFER BOSTRÖM; ELIZABETH CALVERT; HARTVIG CHRISTIE; STEPHEN GRANGER; RICHARD LA LUMIÈRE; NATALIYA MILCHAKOVA; MARIE‐PIERRE OUDOT‐LE SECQ; et al. (Molecular Ecology, 2004)
As the most widespread seagrass in temperate waters of the Northern Hemisphere, Zostera marina provides a unique opportunity to investigate the extent to which the historical legacy of the last glacial maximum (LGM18 000–10 000 years bp ) is detectable in modern population genetic structure. We used sequences from the nuclear rDNA–internal transcribed spacer (ITS) and chloroplast mat K‐intron, and nine microsatellite loci to survey 49 populations (> 2000 individuals) from throughout the species’ range. Minimal sequence variation between Pacific and Atlantic populations combined with biogeographical groupings derived from the microsatellite data, suggest that the trans ‐Arctic connection is currently open. The east Pacific and west Atlantic are more connected than either is to the east Atlantic. Allelic richness was almost two‐fold higher in the Pacific. Populations from putative Atlantic refugia now represent the southern edges of the distribution and are not genetically diverse. Unexpectedly, the highest allelic diversity was observed in the North Sea–Wadden Sea–southwest Baltic region. Except for the Mediterranean and Black Seas, significant isolation‐by‐distance was found from ~150 to 5000 km. A transition from weak to strong isolation‐by‐distance occurred at ~150 km among northern European populations suggesting this scale as the natural limit for dispersal within the metapopulation. Links between historical and contemporary processes are discussed in terms of the projected effects of climate change on coastal marine plants. The identification of a high genetic diversity hotspot in Northern Europe provides a basis for restoration decisions.

Neuroimaging of multisensory processing in vision, audition, touch, and olfaction - Thomas Thesen; Jonas F. Vibell; Gemma A. Calvert; Robert A. sterbauer (Cognitive Processing, 2004)

Three-dimensional mapping of a landslide using a multi-geophysical approach: the Quesnel Forks landslide - A. Bichler; P. Bobrowsky; M. Best; M. Douma; J. Hunter; T. Calvert; R. Burns (Landslides, 2004)

Mapping Expert Knowledge: Redesigning the Monarch Butterfly Biosphere Reserve - Luis A. Bojórquez‐Tapia; Lincoln P. Brower; Guillermo Castilleja; Salvador Sánchez‐Colón; Mariano Hernández; William Calvert; Salomón Díaz; Paola Gómez‐Priego; Georgina Alcantar; Erika Daniela Melgarejo; María José Solares; Liliana Gutiérrez; et al. (Conservation Biology, 2003)
Expert consultation has been used to fill the information gaps that hamper conservation planning and nature reserve design. The use of expert knowledge in conservation planning is difficult, however, because it is subjective, biased, and value‐laden. Decision theory provides a systematic and comprehensive means for addressing experts' subjective—and sometimes contradictory—judgments in the design of nature reserves. Thus, the experts can separate the objective criteria from the subjective components of decision making that place value on those criteria. When linked to a geographic information system ( GIS ), these techniques foster consensus among experts by allowing the exploration of alternative designs in an iterative way. We used such a decision‐analysis approach to redesign the Monarch Butterfly Biosphere Reserve ( MBBR ) in central Mexico. We examined three reserve scenarios to identify the optimal overwintering habitats considering ( 1 ) an area equivalent to the previously defined boundaries of the core zone of the MBBR ( 4500 ha ); ( 2 ) an area equivalent to the previously defined boundaries of the whole MBBR ( 16,000 ha ); and ( 3 ) the maximum possible extent for a new core zone. This last scenario produced an area of 21,727 ha. These results were transferred to the GIS to create the respective nominal maps that were presented to the environmental authorities, who selected the third scenario for the core zone of the new MBBR. Our results allowed us to locate the prime overwintering habitats precisely and to delimit a core area for the reserve that would minimize the inclusion of forest stands valuable to local loggers.

Clinoptilolite zeolite and cellulose amendments to reduce ammonia volatilization in a calcareous sandy soil - Z. L. He; D. V. Calvert; A. K. Alva; Y. C. Li; D. J. Banks (Plant and Soil, 2002)

Hemifacial microsomia: progress in understanding the genetic basis of a complex malformation syndrome - D. Kelberman; J. Tyson; D. Chandler; A. McInerney; J. Slee; D. Albert; A. Aymat; M. Botma; M. Calvert; J. Goldblatt; E. Haan; N. Laing; et al. (Human Genetics, 2001)

New constraints on the pyroclastic eruptive history of the Campanian volcanic Plain (Italy) - B. De Vivo; G. Rolandi; P. B. Gans; A. Calvert; W. A. Bohrson; F. J. Spera; H. E. Belkin (Mineralogy and Petrology, 2001)

Whole-body pre-cooling does not alter human muscle metabolism during sub-maximal exercise in the heat - J. Booth; B.R. Wilsmore; A.D. Macdonald; A. Zeyl; S. Mcghee; D. Calvert; F.E. Marino; L.H. Storlien; N.A.S. Taylor (European Journal of Applied Physiology, 2001)

HLA-B*4034 identified in a UK Caucasoid potential bone marrow donor - Steven T Cox; Franco Tavarozzi; Alasdair McWhinnie; Michael A Hoddinott; Anthony Calvert; Finnuala Baker; J. Alejandro Madrigal; Ann-Margaret Little (Immunogenetics, 2001)

Genetic structure of the world’s polar bear populations - D. Paetkau; S. C. Amstrup; E. W. Born; W. Calvert; A. E. Derocher; G. W. Garner; F. Messier; I. Stirling; M. K. Taylor; Ø. Wiig; C. Strobeck (Molecular Ecology, 1999)
We studied genetic structure in polar bear ( Ursus maritimus ) populations by typing a sample of 473 individuals spanning the species distribution at 16 highly variable microsatellite loci. No genetic discontinuities were found that would be consistent with evolutionarily significant periods of isolation between groups. Direct comparison of movement data and genetic data from the Canadian Arctic revealed a highly significant correlation. Genetic data generally supported existing population (management unit) designations, although there were two cases where genetic data failed to differentiate between pairs of populations previously resolved by movement data. A sharp contrast was found between the minimal genetic structure observed among populations surrounding the polar basin and the presence of several marked genetic discontinuities in the Canadian Arctic. The discontinuities in the Canadian Arctic caused the appearance of four genetic clusters of polar bear populations. These clusters vary in total estimated population size from 100 to over 10 000, and the smallest may merit a relatively conservative management strategy in consideration of its apparent isolation. We suggest that the observed pattern of genetic discontinuities has developed in response to differences in the seasonal distribution and pattern of sea ice habitat and the effects of these differences on the distribution and abundance of seals.

Transport of Phosphorus and Fractionation of Residual Phosphorus in Various Horizons of a Spodosol - Y. C. Li; A. K. Alva; D. V. Calvert (Water, Air, & Soil Pollution, 1999)

Nitrogen isotope fractionation during the uptake and assimilation of nitrate, nitrite, ammonium, and urea by a marine diatom - N. A. D. Waser; P. J. Harrison; B. Nielsen; S. E. Calvert; D. H. Turpin (Limnology and Oceanography, 1998)
Knowledge of the fractionation of nitrogen isotopes by phytoplankton is a key requirement for the calibration of the new δ 15 N paleotracer. An essential part of information required in this calibration concerns the magnitude of isotopic fractionation during the incorporation of N substrates by phytoplankton. To this end, the δ 15 N of batch cultures of Thalassiosira pseudonana grown on nitrate, nitrite, ammonium, and urea was determined. This paper reports the first δ 15 N study of phytoplankton growth on urea (e.g. organic N substrate). The δ 15 N of the particulate nitrogen (PN) collected during the logarithmic growth phase, thus for N‐sufficient cells, was lower than the δ 15 N of the source due to kinetic isotope fractionation. With increasing drawdown of the N substrate, the δ 15 N of the accumulating PN increased in accordance with the Rayleigh distillation model. Enrichment factors (ε) derived from a least‐squares analysis of the accumulated δ 15 N PN data were 5.2 ± 0.2‰, 0.9 ± 0.6‰, 20 ± 1‰, and 0.8 ± 0.6‰ for NO 3 − , NO 2 − , NH 4 + , and urea incorporation, respectively. Overall, ε values for nitrate incorporation were consistent with field estimates of ~6‰ and could be used to estimate past relative nitrate utilization as estimated from the 615N of bulk sedimentary organic matter.

Comparison of Colombian and Costa Rican Strains of Rice Hoja Blanca Tenuivirus - Joachim R. De Miranda; Bertha-Cecilia Ramirez; Miguel Mun~oz; Ivan Lozano; Ray Wu; Anne-Lise Haenni; Ana M. Espinoza; Lee A. Calvert (Virus Genes, 1997)